Solvent selection for highly reproducible carbon-based mixed-cation hybrid lead halide perovskite solar cells via adduct approach. (15th March 2020) - Keremane, Kavya S.; Prathapani, Sateesh; Haur, Lew Jia; Bahulayan, Damodaran; Adhikari, Airody Vasudeva; Priyadarshi, Anish Anish; Mhaisalkar, Subodh G. Subodh
Highlights: One step solution-processed Cs0.1 FA0.9 PbI3 deposition method for carbon-based PSCs. More industrially acceptable eco-friendly solvent, DMSO via adduct approach. High stability with no discernible decrease in efficiency for 1800 h under ambient. Cs0.1 FA0.9 PbI3  perovskite in carbon based devices exemplifies great potential of PSC. Abstract: The major problem identified in carbon-based mixed cation perovskite solar cells (PSCs) is the selection of a suitable solvent for single-step solution-processed perovskite deposition in order to promote their scalable production. Herein we report a detailed study on the selection of appropriate solvent for the one-step deposition of cesium-formamidinium lead iodide (Cs0.1 FA0.9 PbI3 ) perovskite via Lewis acid-base adduct approach for fully printable mesoporous PSCs with mesoporous TiO2 /ZrO2 /C architecture. Highly reproducible Cs0.1 FA0.9 PbI3 solar cells were fabricated via adducts of PbI2 with eco-friendly dimethyl sulfoxide (DMSO). The best cells fabricated with the above approach yielded a photoconversion efficiency (PCE) of 12.33% for a small area device (active area: 0.09 cm 2 ) and 10.1% for a large area device (active area 0.7cm 2 ). The average power conversion efficiency for 62 PSCs was found to be 10.5% under an AM 1.5G illumination. Finally, the mixed cation perovskite in carbon architecture using the Lewis acid-base adduct approach is remarkably stable, with less than 1% change from the initial PCE after 1800h of storage under dark ambient conditions (25 °C, 60–70% RH).